IMPROVING STUDENT ACTIVITY AND LEARNING RESULTS IN NATURAL SCIENCE CONTENT THROUGH PICTURE AND PICTURE METHOD - Gita Pratiwi; Agung Setyawan (Citra Dharma Cindekia, 2022)
The selection of appropriate learning methods has a major effect on improving the quality of education. The purpose of this study was to determine how much increase in activity and learning outcomes of fourth grade students of SD Negeri Kamal 3 after applying the picture and picture method. The research data was taken using test, observation, and documentation techniques and then analyzed using an interactive model which has three components, namely data presentation, data reduction, and drawing conclusions. The results of this study indicate an increase in the score of student activity and learning outcomes after applying the picture and picture method. At the end of the cycle the percentage of students who actively asked, answered, and carried out the teacher's orders achieved high scores of 87%, 93%, and 93%, respectively. At the end of cycle II, it also shows that all students have finished studying so that the class can be said to have completed classically. Based on the results of this study, it can be concluded that the application of the picture and picture method can increase the activity and learning outcomes of fourth grade students at SD Negeri Kamal 3